Adoption of social media as distribution channels in tourism marketing: A qualitative analysis of consumers' experiences - Chryssoula Chatzigeorgiou; Evangelos Christou (Journal of Tourism, Heritage & Services Marketing, 2020)
The study reported in this paper explores consumers' experiences with technology-assisted service encounters by investigating the applicability of Mick and Fournier's paradoxes of technology adoption to the social media as distribution channel in tourism scenario. In-depth interviews were conducted to explore consumers' experiences when using social media distribution services and the results were compared to those of Mick and Fournier. The findings are similar, suggesting that when consumers adopt online technology like social media, they can simultaneously develop positive and negative attitudes. The findings of this study also suggest that the nature of some of the paradoxes experienced by consumers may depend on the industry (tourism in this study) and the technology (social media in this study) being investigated.
Keywords: L83; M1; O14; Z33; 330; adoption of technological innovations; social media; distribution channels; tourism marketing